HUSBAND’S PARTICIPATION IN PRENATAL CLASS: A SCOPING REVIEW - Suryaningsih, Endang Koni; Fauzianty, Ariska; Nguyen, Tuan Van; Kusuma, Nur Intan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Much of the prenatal class review has focused on identifying and evaluating the effectiveness of mother’s participation to their own pregnancy outcome, however, there is a relatively small body of literature that is concerned with husband’s participation during the prenatal class. Many studies highlighted the implication of husbands' participation of childbirth to the mother’s pregnancy outcome. This research is a scoping review using Arksey O'Malley Framework and PRISMA-ScR Checklist. The literature search in this study used two databases, namely Pubmed and Science Direct, and a search engine, namely Google Scholar. The keywords used are role or participation, husband, and a prenatal class. Assessment of article quality using Hawker Tools. Of the 988 potentially relevant articles, four articles are relevant. The research articles come from 2 different countries and quantitative methods. The mapping of the themes obtained is the support of spouses and the participation of husband and wife in prenatal class. The need for active husband support to improve the quality of life of mothers during pregnancy, childbirth, and postpartum. Needed for active husband support to improve the quality of life of mothers during pregnancy, childbirth, and postpartum.